NANOTERAPÊUTICOS TÓPICOS PARA O TRATAMENTO DA ACNE VULGAR: IMPACTOS CIENTÍFICO E TECNOLÓGICO - Santos, Zípora Morgana Quinteiro dos (2021)
Acne vulgaris is currently the most prevalent skin disease in the world. It is treated topically with antibiotics, retinoids, bactericides, seborregulators and keratolytics. The clinical use of these products is lacking in more in-depth clarifications of their etiopathophysiology, active ingredients, effects and nanostructures as well as of the institutions and countries involved in their research, development and innovation. The objective of this research was to conduct a technological prospection of topical nanotherapeutics with emphasis on nanocosmetics applied to the treatment of acne vulgaris through the analysis and review of scientific articles and patent applications. The Web of Science and Scopus databases and the Lens.Org (2020) program were used for the data collection and documentary research. The results of the literature search indicate that this pathology has inflammatory, multifactorial and recurrent characteristics. In 2015, global expenditure with the treatment of this pathology represented >10% of the overall expenditure in the treatment of skin diseases. It is estimated that by 2023, the cosmetics industry will reach US$805.61 billion and the global nanocosmetics market will grow at an average rate of 16.6% each year. The selected patent applications can be found in Section A, subclasses A61K, A61Q, and A61P, categorized according to the International Patent Classification. Lipotec, Sederma and Lubrizol are the companies that have filed the most patent applications, respectively. The United States is the country that files most patent applications. India is the country that publishes the most scientific papers. Both the papers and patents show interest in Retinoic Acid, Adapalene and Benzoyl Peroxide derivatives. The same interest was found in research institutions and companies, in addition to the interest of research institutions in publishing research involving substances of natural origin. Brazil and Iran rank 2nd in the survey of countries that published the most articles on this subject. There is a relationship between articles and patents about nanostructures: nanostructured lipid carrier, liposomes and niosomes. Prospective studies are important to support decision making. These results can serve as an informative source to establish the state of the art of the subject; to guide innovative efforts and allocate financial resources; and to stimulate new and more in-depth studies, given the importance of innovation in the economic context, the relevance of the nanocosmeceutical sector, the peculiarities of nanotechnology, and the social character inherent in global innovations in the topical treatment of acne vulgaris.